Safety of milrinone use in neonatal intensive care units. Issue 1 (January 2015) - Samiee-Zafarghandy, Samira; Raman, Sudha R.; van den Anker, John N.; McHutchison, Kerstin; Hornik, Christoph P.; Clark, Reese H.; Brian Smith, P.; on behalf of the Best Pharmaceuticals for Children Act—Pediatric Trials Network Administrative Core Committee, 1
Abstract Background Milrinone use in the neonatal intensive care unit has increased over the last 10 years despite a paucity of published safety data in infants. We sought to determine the safety of milrinone therapy among infants in the neonatal intensive care unit. Methods We conducted a retrospective data analysis, identifying all infants who were exposed to milrinone and discharged from 322 neonatal intensive care units managed by the Pediatrix Medical Group from 1997–2010. We identified adverse events (AEs) during milrinone exposure. The unit of observation for clinical AEs was the first course of milrinone and for laboratory AEs it was an infant-day of exposure to milrinone. Results Overall, 1446 of 716, 821 (0.2%) infants received milrinone for a total of 6894 infant-days. The proportion of infants exposed to milrinone increased from 0 in 1997 to 4/1000 infant cases in 2010. Persistent pulmonary hypertension (40%) was the most commonly reported diagnosis at the start of milrinone administration. Overall, 606/1446 (42%) of infants had at least 1 clinical AE recorded during milrinone therapy. Hypotension requiring pressors and thrombocytopenia (< 100, 000/mm3) were the most commonly reported clinical and laboratory AEs, respectively. Death was reported in 8% of infants during the first course of milrinone therapy. Conclusion Among infants hospitalized in the neonatal intensive care unit, there was an increase in the use of milrinone over the past 13 years. The safety, dosing, and efficacy of milrinone in infants should be determined in prospective clinical trials.